2013
DOI: 10.4028/www.scientific.net/amm.330.158
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electric Energy Consumption Patterns: A Case Study of a Real Life Office Building

Abstract: Electric energy consumption shares a great portion of commercial building energy. Electric energy saving is essential to reduce total energy consumption in commercial buildings. To draw energy saving methods, it is necessary to monitor real energy consumption patterns and analyze the results. We monitor the lighting and non-lighting energy consumption of eleven zones in a real working office building every fifteen minutes during eleven months. We observe and analyze the monthly and daily energy consumption pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Many works have shown that the integration of such devices alongside a controller is able to achieve significant savings in energy consumption. Simulations have shown that it is possible to achieve energy savings of up to 38% with occupancy sensors compared to manual switching [5,6] while an occupation study by Han et al reports possible savings of up to 40% [7]. An experimental study done by Jennings et al reports 20-26% savings [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many works have shown that the integration of such devices alongside a controller is able to achieve significant savings in energy consumption. Simulations have shown that it is possible to achieve energy savings of up to 38% with occupancy sensors compared to manual switching [5,6] while an occupation study by Han et al reports possible savings of up to 40% [7]. An experimental study done by Jennings et al reports 20-26% savings [8].…”
Section: Introductionmentioning
confidence: 99%